Academic Management System at SD Darul Hikam Bandung - Yana, Hana Ervi; Hana, Muhammad Faishol; Fadli, Nanang Nur; Alfia, Ulfa; Hanik, Elya Umi (Lembaga Pendidikan Hikmatun Najah Blora, 2022)
This study aims to determine the role of the academic management system which includes the role and quality of teachers, curriculum, infrastructure and achievements of students at SD Darul Hikam Bandung. The method used in this research is descriptive qualitative, namely data in the form of descriptive information in the form of prose language which is then linked with other data to get clarity on a truth. The results showed that the academic management system which includes the role and quality of teachers, curriculum, infrastructure and student achievement at SD Darul Hikam Bandung is very concerned. SD Darul Hikam also uses a distinctive curriculum, namely Taqwa Character Building (TBC), which is different from other schools, so that SD Darul Hikam can be used as a competent reference school compared to other schools.